2006
DOI: 10.1007/s10567-006-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parenting and Maltreatment Histories in Unipolar and Bipolar Mood Disorders: Mediation by Cognitive Vulnerability to Depression

Abstract: In this article, we review empirical research on the role of individuals' parenting and maltreatment histories as developmental antecedents for symptoms and diagnosable episodes of unipolar and bipolar spectrum disorders. Our review is focused on the following three overarching questions: (1) Do negative parenting and a history of maltreatment contribute risk to symptoms or diagnosable episodes of unipolar and bipolar disorders? (2) Are the associations of negative parenting and maltreatment histories with bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
159
1
17

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 171 publications
(323 reference statements)
13
159
1
17
Order By: Relevance
“…This study suggests the possibility that childhood abuse might increase soft bipolarity in the general adult population, which, in turn, might affect the pathogenesis or clinical outcomes of mood disorders. Several studies have reported that the history of childhood abuse is closely related to the onset, course, and treatment response of mood disorders (Alloy et al, 2006;Caspi et al, 2003;Daruy-Filho et al, 2011;Levitan et al, 1998;Nanni et al, 2012). The results of this study link childhood abuse to affective temperaments in aspects of depressive symptoms.…”
Section: Discussionsupporting
confidence: 52%
“…This study suggests the possibility that childhood abuse might increase soft bipolarity in the general adult population, which, in turn, might affect the pathogenesis or clinical outcomes of mood disorders. Several studies have reported that the history of childhood abuse is closely related to the onset, course, and treatment response of mood disorders (Alloy et al, 2006;Caspi et al, 2003;Daruy-Filho et al, 2011;Levitan et al, 1998;Nanni et al, 2012). The results of this study link childhood abuse to affective temperaments in aspects of depressive symptoms.…”
Section: Discussionsupporting
confidence: 52%
“…Ainda, quando existe trauma na infância, as estratégias de enfrentamento e regulação do humor ficam prejudicadas (Pfeiffer, Kaemmerer, Mearns, Catanzaro & Backenstrass, 2011). Alloy et al (2006) descreve que indivíduos com transtorno de humor bipolar I, com histórico de maus-tratos, têm uma versão agravada do seu transtorno de humor. Esses dados corroboram achados que apontam para uma possível associação entre episódios de mania com casos de violência infantil (Zavaschi, Graeff, Menegassi, Mardini, Pires, Carvalho et al, 2006).…”
Section: Métodounclassified
“…Nesse sentido, o trauma na infância tem sido indicado como fator associado a transtornos do humor (Alloy, Abramson, Smith, Gibb & Neeren, 2006). Ainda, se o trauma na infância está associado a uma história familiar positiva de transtorno do humor, as chances de desenvolvimento se tornam maiores.…”
Section: Introductionunclassified
“…When examining this, it may be prudent to measure the parent′s impairment in areas that are more salient to offspring, such as family processes. A large corpus of research has implicated factors such as parent-offspring conflict (Rueter et al, 1999), adverse family environments (Eley et al, 2004;Sander and McCarty, 2005), parenting behaviour (Alloy et al, 2006), and marital difficulties (Cummings et al, 2005;Downey and Coyne, 1990) in the onset and maintenance of offspring depressive symptoms. Whilst time constraints of research and clinical protocols preclude the use of separate questionnaires to assess each domain of familial functioning, incorporating elements of this research into an impairment questionnaire for parents may be pertinent when assessing intergenerational transmission of depression.…”
Section: Introductionmentioning
confidence: 99%